The place of domestic adventure parks in the sports services, in connection with university student’s research - Boda, Eszter; Bácsné Bába, Éva; Szabados, György; Müller, Anetta (Studia Mundi – Economica, 2018)
In modern world, quality leisure spending is increasingly motivated by the enjoyment of experience and the presence of natural factors. We have been researching the relationship between leisure time and adventure park visit among university students. During our research we used questionnaires to find answers (n=408). We have found significant differences in the activity of leisure time and, for example, in the preference of cultural leisure programs. We are trying to make the results available so that adventure parks can use to organize their program offerings.